Potential Liability Of Bloggers In Defamation As Online Intermediaries: A Comparative Study Of The Position In Malaysia And The Uk - Nazli, Ismail@Nawang; Aminuddin, Mustaffa; Mohd Lotpi, Mohd Yusob (2017)
Online intermediaries play an important role in publication of information on the Internet as they generally perform one of three functions, namely as mere conduits, caches or hosts of information. These intermediaries have been categorically classified into connectivity intermediaries such as Internet service providers (ISPs), navigation intermediaries such as Google, and commercial and social networking providers and other hosts such as Wikipedia, Facebook, Twitter, blogs and many others. Since Web 2.0 platforms and other content hosts including blogs are easier to trace and often operate locally, they appear as an easy target in defamation suit as they represent a point of control or gatekeeper over materials on the Internet. This has resulted in undesirable consequences for bloggers as they are likely to be exposed to defamatory postings by third parties. As such, this study will embark on the study of potential liability of bloggers as online intermediaries in relation to third party defamatory content